A correlational study on patient satisfaction and the quality of the complete dentures done by the University of the Philippines College of Dentistry (UPCD) clinical dentistry 40 students on SY 2003-2004 - Ayam, Mary Charlotte S.; Teano, Emma Cecilia A.; Santos, Jessica K.R. (Adviser).
This study aimed to relate patient satisfaction with, the quality of the dentures done by UPCD Clinical Dentistry 40 students on the SY 2003-2004. Out of the 65 complete denture patients on that school year, 27 were included in the study of which 22 of them participated. To determine if the subjects were satisfied, comfortable, able to speak and masticate well, and were pleased with their esthetic appearance, survey questionnaires were handed out for them to answer. As for the quality of the dentures, clinical inspections were performed by the examiner. Results showed that for the quality of the dentures, there is an equal percentage of 50% (11 each) for good quality and not-so-good quality dentures. Eighteen (82%) respondents were satisfied with their dentures, 11 of which have good quality dentures while 4 (18%) respondents were found to be dissatisfied. Statistics showed that there is a linear relationship between the overall satisfaction and the overall quality of the dentures. Hence, a positive correlation exists between good overall quality of dentures and overall patient satisfaction, meaning, a good quality denture yields a satisfied patient.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Patient satisfaction; Complete dentures